Surface modification of Luffa and Maize fibers by using alkali medium - Fahmida-E- Karim; Md. Redwanul Islam; Muhtasim Habib Supto; Abdullah Al Mamun Rafi; Tanima Rahman Tanni; Hosne Ara Begum (Cleaner Engineering and Technology, 2024)
Agricultural biomass is a well-known renewable resource that has a high rate of recycling. Two of them are luffa sponge and corn husk/maize fibers. Luffa sponge may be effectively used to reinforce lightweight composite constructions because of its polypore structure. For this race, maize fiber is also appropriate. Surface modifications for both of the fibers are needed for increasing mechanical strength with higher interfacial bonding with the matrix materials of composite manufacturing. This investigation involved treating both materials with 5 g/L, 10 g/L, and 15 g/L of NaOH in order to describe the alterations occurring on their physio-chemical characteristics. The therapy lasted 60 min and was administered at 90 °C. Following that, acetic acid was used to neutralize the samples. The ASTM D1445 technique was used to measure the bundle fibers' breaking force and elongation, and the ASTM D570 procedures were used in order to determine the water absorption variation % in the treated samples. The FTIR test and SEM examination revealed the contaminants that were eliminated from the surface of Luffa and Maize fibers. The test findings demonstrated improved modification behaviors for the 15 g m/L treated fibers, which had an elongation percentage of 3.02% and an equivalent breaking force of 5.12 kg for the Luffa fiber and 5.72 kg for the maize fiber. Natural contaminants were eliminated as a result of variations in functional group intensity shown in the FTIR pictures. However, SEM pictures showed that the surface smoothed out for samples treated with 15 g per liter of NaOH, which may be the cause of the fiber's brittle interlocking with the matrix components. Moreover, water absorbency rose by over 300% compared to the untreated fibers. In summary, samples treated with 10 g/L NaOH might serve as superior reinforced materials of composite for both types of fibers.